Flavonoids and antioxidant activity of Rosa agrestis leaves - BİTİŞ, LEYLA (TAYLOR & FRANCIS LTD, 2010)
In this work we report the isolation and characterisation of seven flavonoids, the levels of total phenolics, flavonoids and proanthocyanidins, and the antioxidant activity of the leaf extract of Rosa agrestis Savi (Rosaceae). The results showed that the R. agrestis leaf extract exhibited significant antioxidative activity as measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) (EC50 = 47.4 mu g mL-1), inhibited both -carotene bleaching and deoxyribose degradation, quenched a chemically generated superoxide anion in vitro and showed high ferrous ion chelating activity. Reactivity towards 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt (ABTS) radical cation and ferric-reducing antioxidant power (FRAP) values were equivalent to 2.30 mM L-1 Trolox, the water soluble -tocopherol analogue, and 1.91 mM L-1 Fe2+, respectively. The high antioxidant activity of the extract appeared to be attributed to its high content of total phenolics, flavonoids and proanthocyanidins. The flavonoids isolated from R. agrestis leaves were diosmetin, kaempherol, quercetin, kaempherol 3-glucoside (astragalin), quercetin 3-rhamnoside (quercitrin), quercetin 3-xyloside and quercetin 3-galactoside (hyperoside). Diosmetin (5,7,3'-trihydroxy-4'-methoxyflavone) was isolated for the first time from Rosa species.
Keywords: antioxidant activity; flavonoids; polyphenol content; Rosa agrestis; EXTRACTS; POLYPHENOLS; L.